O mercado do futebol: dimensões institucionais e desempenho econômico - Correia, Fabiana Barros (2020)
This research aims to analyze how the process of formation and triggering of the football market occurred and what its implications for the Brazilian scenario. It is a theoretical research, complemented by data made available on public and private bases. The research is descriptive, since it intends to characterize the Brazilian soccer market, and it is explanatory for identifying the conditions and causal factors, originated in the past, which imply the patterns inherent to the Brazilian market. Soccer is a sporting activity with an imprecise origin, but its initial characteristics go back to ideas focused on playful aspects, with the presence of affective ties, fun and leisure. In the historical development process, sport came to be seen as an ostentatious activity, since it became an activity of prowess, practiced essentially by the idle class. From the feeling of emulation of the feat in sport, emanated by the common classes, there was the popularization of this sports activity, transforming it into a sport of the masses. Through popularization, and subsequent professionalization, a specific market was created, aimed at exploring the feat and social status demanded by the new bias acquired by sport. The organization, through legal changes and creations, structural changes, and mechanisms, conditions the renewal of the sport and its transformation into a profitable market with significant financial figures. The soccer product results from the interaction of agents in the hierarchical productive chain of soccer, committed to the production processes, organization and management of the spectacle product. The football product is created from the joint participation of the teams, the teams individually do not compete economically with each other, but rather, all of them together. It is the league that competes as a production chain with other alloys. Here, competition occurs between sports, and demonstrates, whether by seasonal aspects or by social classes, consumer-fan preferences. The substitute products next to each other are sports, as products offered by each League. The teams' interest is to achieve good sporting and financial performances, and to gain loyalty to football, specifically. The intention, therefore, is to provide competitive and attractive games in order to win the loyalty of its consumer / supporter for the soccer games, that is, the soccer league, to the detriment of other leagues. When seeking to understand the Brazilian football scene, there is an increase in revenues from advertising, box office, game broadcasts and athletes' negotiations, even in a period with national economic stagnation. This testifies to the success of the sales effort mechanisms applied by the soccer production chain. Competition between leagues falls on the dynamics of sales efforts, which reflects an increase in the audience for game broadcasts, increased tickets, more profitable advertising and advertising contracts, among other ways of increasing revenues and profits. This condition reveals a promising market, with potential for growth, since even in the face of economic stagnation, the financial flow of football is maintained.